KOMPARASI SISTEM PINDAH TANAM DAN TANAM BENIH LANGSUNG BUDIDAYA TANAMAN PADI (Oryza sativa L.) DI DESA RANTEWARINGIN-KEBUMEN, JAWA TENGAH - Vicky Virdaus Mulyadi; Ahmad Rifqi Fauzi; M. Rizal Taufikurrahman (Agrin, 2022)
Rice is a strategic commodity for Indonesia and needs to increase its production with an efficient cultivation system to face limited water and labor in the future. The transplanting system (TPR) was a popular method for rice cultivation in Indonesia, and it needed too much input. On another side, direct seeding (DSR) has long been known and considered more efficient in labor and water used. This study aims to determine the comparison of cultivation methods of TPR and DSR, which are more profitable among farmers in Rantewringin village, and to determine an efficient cultivation system. This research was carried out in August-September 2020. The methods used were qualitative and quantitative, sampling was purposive sampling, and the analysis tools used farm analysis and SWOT. The results of the feasibility analysis that has been carried out, the acceptance value of the Tapin system is greater than the Tabela system, but the profit of the Tabela system is higher than the Tapin system. The results of the farming analysis show that the feasibility of farming, the Tapin system, and the Tabela system are feasible (R/C ratio > 1). Analysis of the IFAS and EFAS shows that the Tapin system has the power to produce better growth in water-sufficient conditions but is threatened in a water- and labor-constrained position. Meanwhile, Tabe cultivation has the power to be carried out in limited water conditions and is efficient in using labor. The analysis results indicate that Tabela cultivation can be an efficient and profitable alternative technology in conditions of lack of water. The development of the Tabela system is still needed for broader application.